2017
DOI: 10.1016/j.exphem.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation between hepcidin and erythropoiesis and its therapeutic application in erythroid disorders

Abstract: Iron is required for hemoglobin production, and it plays a key role during erythropoiesis. Systemic iron homeostasis is mainly negatively regulated by the peptide hormone hepcidin, coded by the gene HAMP. Hepcidin excess may cause iron deficiency, iron-restricted erythropoiesis, and anemia. Conversely, hepcidin insufficiency leads to iron overload and oxidative damage in multiple tissues. During regulation of hepcidin synthesis, multiple promoter elements in the HAMP gene respond to variable signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…EPO and other factors secreted by erythroid cells, such as GDF15, have been proposed to inhibit liver hepcidin expression [17,30]. We found that GDF15 was increased in hemodialysis patients (Table 2), and, thus, may contribute to a repressing effect on hepcidin expression, and to explain the inverse association between ESA dose and hepcidin levels that we found.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…EPO and other factors secreted by erythroid cells, such as GDF15, have been proposed to inhibit liver hepcidin expression [17,30]. We found that GDF15 was increased in hemodialysis patients (Table 2), and, thus, may contribute to a repressing effect on hepcidin expression, and to explain the inverse association between ESA dose and hepcidin levels that we found.…”
Section: Discussionmentioning
confidence: 50%
“…Hepcidin induces endocytosis and proteolysis of ferroportin on duodenal enterocytes, reducing iron absorption; and on the membrane of macrophages and hepatocytes, reducing the efflux of iron from the major iron stores, for erythropoiesis [16]. Hepatic hepcidin synthesis is up-regulated by inflammation, through interleukin (IL)-6, transferrin saturation, and liver iron levels, while increasing erythropoietin (EPO), erythropoiesis, and hypoxia down-regulate hepcidin synthesis [17]. Some factors secreted by erythroid cells along the erythropoietic process, such as growth differentiation factor 15 (GDF15) and erythroferron, have also been implicated in the suppression of hepcidin expression [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During erythropoietic stimulation, such as in conditions associated with anaemia, hypoxia or during erythropoietin (EPO) administration, HAMP expression is decreased, resulting in increased iron availability for erythropoiesis. This effect is thought to result from factors secreted by erythroid precursors (Shenoy et al , ; Wang et al , ). Several potential candidate ‘erythroid factors’ have been identified.…”
mentioning
confidence: 99%
“…Accordingly, hepcidin and its expression regulators have been studied as targets for potential therapeutic agents. For example, antibodies, agonists, or antagonists of hepcidin, cytokine receptor antibodies and small‐molecules that modify hepcidin expression, are under investigation or in the process of development as novel therapeutics for these iron disorders . Advances in hepcidin‐targeting therapeutic studies and also an updated understanding of how hepcidin plays crucial roles in systemic iron homeostasis have been recently well‐documented elsewhere.…”
Section: Introductionmentioning
confidence: 99%